Obesity studies in the circumpolar Inuit: a scoping review - Tracey Galloway; Hilary Blackett; Susan Chatwood; Charlotte Jeppesen; Kami Kandola; Janice Linton; Peter Bjerregaard (International Journal of Circumpolar Health, 2012)
Background. Among circumpolar populations, recent research has documented a significant increase in risk factors which are commonly associated with chronic disease, notably obesity. Objective. The present study undertakes a scoping review of research on obesity in the circumpolar Inuit to determine the extent obesity research has been undertaken, how well all subpopulations and geographic areas are represented, the methodologies used and whether they are sufficient in describing risk factors, and the prevalence and health outcomes associated with obesity. Design. Online databases were used to identify papers published 1992–2011, from which we selected 38 publications from Canada, the United States, and Greenland that used obesity as a primary or secondary outcome variable in 30 or more non-pregnant Inuit (“Eskimo”) participants aged 2 years or older. Results. The majority of publications (92%) reported cross-sectional studies while 8% examined retrospective cohorts. All but one of the studies collected measured data. Overall 84% of the publications examined obesity in adults. Those examining obesity in children focused on early childhood or adolescence. While most (66%) reported 1 or more anthropometric indices, none incorporated direct measures of adiposity. Evaluated using a customized quality assessment instrument, 26% of studies achieved an “A” quality ranking, while 18 and 39% achieved quality rankings of “B” and “C”, respectively. Conclusions. While the quality of studies is generally high, research on obesity among Inuit would benefit from careful selection of methods and reference standards, direct measures of adiposity in adults and children, studies of preadolescent children, and prospective cohort studies linking early childhood exposures with obesity outcomes throughout childhood and adolescence.